Proximités géographiques et distances culturelles entre la ville et l’agriculture - Roland Vidal (Projets de Paysage)
The emergence of the landscape in the Western culture has been accompanied by keeping the farming world at a distance, a world of which the aesthetic qualities have been recognized, but of which we refused to understand the social, technical, and economic functioning – the one that made the daily reality of those who inhabited it : the farmers. With the modernisation of agriculture, and the disappearance of the horticultural belt, the expanding city finds itself in a new situation of immediate proximity with a world that it still ignores : the one of cereal growing. The border between the two worlds have become moving and uncertain territories always waiting for new projects. Referring to the example of the Parisian urban area, we will try to put things in perspective and differentiate the utopias, which by perpetuating « the debarment of land working» that accompanied the construction of our landscape culture, still nourish many plans, and what could be a new way of conceiving enduring urban areas.